Optimización de la producción, tiempos y movimientos en el proceso de construcción de implementos agrícolas - Chuqui Achig, Danys Wilfrido (2017)
The study of times and movements in the process of construction of agricultural implements Moreano S.A. In which the process of construction of the towed dredges is analyzed, recording the times and movements of the production stages starting from the collection of the material, tracing, cutting, armado, dotted, displacement, topped and inspection of the towed dredges. Identifying that in the construction of the base bed of the towed dredges is used more time in the stages of cutting and arming. The personnel working in these areas of work don´t know very well of the activities as they were identified at the time of conducting a previous survey, for the lifting of the times was done with the methods by timing with which they were established the time of each work area, obtaining a total of 26:08:27 of time employed, at a cost per drag of $ 2995.83. For the reduction of time and movement, a training was proposed for the personnel production of the company in regard to management of machinery and tools, through the training carried out, the times were reduced in the construction of agricultural towed dredges at 21:48:37 at a cost of $ 2939.28....